The current state of stem cell therapy for ocular disease. (December 2018) - Bobba, Samantha; Di Girolamo, Nick; Munsie, Megan; Chen, Fred; Pébay, Alice; Harkin, Damien; Hewitt, Alex W.; O'Connor, Michael; McLenachan, Samuel; Shadforth, Audra M.A.; Watson, Stephanie L.
Abstract: Herein, we review the safety, efficacy, regulatory standards and ethical implications of the use of stem cells in ocular disease. A literature review was conducted, registered clinical trials reviewed, and expert opinions sought. Guidelines and codes of conduct from international societies and professional bodies were also reviewed. Collated data is presented on current progress in the field of ocular regenerative medicine, future challenges, the clinical trial process and ethical considerations in stem cell therapy. A greater understanding of the function and location of ocular stem cells has led to rapid advances in possible therapeutic applications. However, in the context of significant technical challenges and potential long-term complications, it is imperative that stem cell practices operate within formal clinical trial frameworks. While there remains broad scope for innovation, ongoing evidence-based review of potential interventions and the development of standardized protocols are necessary to ensure patient safety and best practice in ophthalmic care. Highlights: Limbal stem cell transplantation is a viable therapy based on Phase I/II clinical trials. Further pre-clinical and clinical studies of other cell sources for ocular stem cell transplantation should be conducted. It is imperative that stem cell practices operate within formal clinical trial frameworks.